1999
DOI: 10.1159/000027711
|View full text |Cite
|
Sign up to set email alerts
|

Microradiographic Study of Retrieved Craniofacial Osseointegrated Implants

Abstract: In this study 18 screw-shaped extraoral osseointegrated implants retrieved from 10 patients were analyzed. The reasons for retrieval were: unexplained pain (n = 4); inability to cope with the implants (n = 2); fracture of the central screw (n = 2); skin penetration problems (n = 1), and trauma (n = 1). Retrieved implants were trephined with a border of surrounding bone, fixed, embedded in epon plastic, ground and processed for microradiography. The study group comprised 6 males and 4 females with a mean age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Bone–metal contact varied between 30 and 70%. In a study of 18 osseointegrated implants retrieved from 10 patients, three of the implants were from an irradiated patient (22). It was found that bone–metal contact was reduced (27–35.6%) compared to nonirradiated implants of the same region, which showed 44–46.6% bone–metal contact.…”
Section: Implant Failures In Relation To Regionmentioning
confidence: 99%
“…Bone–metal contact varied between 30 and 70%. In a study of 18 osseointegrated implants retrieved from 10 patients, three of the implants were from an irradiated patient (22). It was found that bone–metal contact was reduced (27–35.6%) compared to nonirradiated implants of the same region, which showed 44–46.6% bone–metal contact.…”
Section: Implant Failures In Relation To Regionmentioning
confidence: 99%
“…In a study of 18 osseointegrated implants retrieved from 10 patients, three of the implants were from an irradiated patient. 29 It was found that BMC was reduced (27)(28)(29)(30)(31)(32)(33)(34)(35).6%) compared to nonirradiated implants of the same region that showed 44-46.6% BMC. As a comparison average, the BMC for loaded extraoral implants was estimated to be 62% by Bolind and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Factors influencing dental implant success or failure can be classified as extrinsic or intrinsic. Extrinsic causes cited in the literature include contiguous use of local carcinogens, such as tobacco, higher doses of radiation, and chemotherapy . Intrinsic causes impacting dental implant failure are that of soft tissue status, shorter implants, and bone stock .…”
Section: Discussionmentioning
confidence: 99%